Therapeutic potential of Anacyclus pyrethrum aqueous extract in managing Clonazepam withdrawal in rats - Abdelmounaim Baslam, Hamid Kabdy, Mehdi Aitlaaradia, Jawad Laadraroui, Sara Oufquir, Rachida Aboufatima, Samia Boussaa, Abderrahman Chait (Journal of Applied Pharmaceutical Science, 2024)
The management of benzodiazepine withdrawal syndrome is challenging, and there is currently no consensus on the optimal treatment approach. Our study aims to investigate the possible effect of the aqueous extract of Anacyclus pyrethrum (AEAP) on Clonazepam dependence in rats via the measurement of oxidative stress, behavioral and biochemical changes. Dependence was induced by chronic administration of Clonazepam for 30 days, then AEAP was administered orally to rats. Withdrawal syndrome was assessed employing the conditioned place preference test, behavioral tests, and biochemical assays. Oxidative stress was evaluated by measuring levels of malondialdehyde (MDA), catalase (CAT), and superoxide dismutase (SOD). The percentage of open-arm entries, time spent in open arms decreased, and immobility time increased significantly among the Clonazepam-dependent group from the preconditioning to withdrawal phase (p < 0.001). The cortisol level was higher among Clonazepam group, the MDA increased, and CAT and SOD measurements demonstrated a notable decrease in the Clonazepam withdrawal group. AEAP administration at a dose of 200 mg/kg significantly alleviated anxiety and depression-like behaviors and led to a substantial decrease in oxidative stress levels during Clonazepam withdrawal, demonstrating the beneficial impact of AEAP. The use of Anacyclus pyrethrum may provide a novel therapeutic approach for managing the adverse effects of Clonazepam dependence by targeting oxidative stress.
Keywords: Anacyclus pyrethrum, benzodiazepine, clonazepam, conditioned place preference, physical dependence, oxidative stress, substance use disorders